Pengaruh Sistem Informasi Akuntansi dan Digitalisasi Keuangan terhadap Transparansi Pengelolaan Dana Desa di Desa Batu Kalung - Nia Apiska; Herlin; Aji Sudarsono (Politeknik Raflesia Press, 2026)
This study aims to determine the effect of accounting information systems (X1) and financial digitalization (X2) on the transparency of village fund management (Y). The research was conducted using a quantitative method with primary data obtained from questionnaires distributed to 120 respondents involved in village fund management. Data analysis was carried out using multiple linear regression through the Kolmogorov-Smirnov normality test, heteroscedasticity test, multicollinearity test, and hypothesis testing (t-test and F-test) with the help of SPSS version 22. The results of the study show that Accounting Information Systems and Financial Digitalization have a positive and significant effect on Village Fund Management Transparency. This finding emphasizes that the implementation of a good accounting information system enhances accountability and public trust, while financial digitalization promotes efficiency and information transparency. Thus, it can be concluded that the better the implementation of accounting information systems and the more optimal the financial digitalization, the higher the level of transparency in village fund management